Research on the Application of BIM Technology in Building Electrical Design - Chen , Qiang (Journal of Theory and Practice of Engineering Science, 2023)
In recent years, BIM technology has been widely used in the field of construction engineering at home and abroad. As a new type of building science and technology, it can better help related personnel to deal with the construction of the complex form of building construction work, and has a positive effect on the further development of the construction industry. According to the actual situation, the application of BIM technology is still in the initial stage. The application of BIM technology during the process of building electrical design is analyzed and discussed accordingly, and the application process and problems of BIM technology in the process of building electrical design are summarized.